Investigation of some DNA repair genes association in non small cell lung cancer - Coskunpinar, E; Yildiz, P; Aynaci, E; Turna, A; Musteri Oltulu, Y; Hekimoglu, E; Isbir, T; Yaylim, I (Cellular and Molecular Biology, 2015)
Ribonucleoside-diphosphate reductase subunit M2, also known as ribonucleotide reductase small subunit, is an enzyme that in humans is encoded by the RRM2 gene and also Ribonucleoside-diphosphate reductase large subunit is an enzyme that in humans is encoded by the RRM1 gene. RRM1 is a gene important in determining tumor phenotype, but also induced the expression of PTEN tumor suppressor gene, cell migration, invasion and metastasis formation, and play a preventive role. ERCC2 DNA repair mechanism is associated in more than 20 genes involved in the NER pathway. The aim of this study is to investigate rs13181 ERCC2 (T>G) (Lys751Gln), rs12806698 RRM1 (-269C>A) and rs6759180 (located in the 5'UTR) RRM2 (10126436G>A) gene polymorphisms by using real time PCR technique in patients with NSCLC. 193 NSCLC cases and 141 healthy control cases were included in this study. A significant difference was found between rs12806698 RRM1 genotype distributions (*p: 0.034) and were determined increases the risk of disease approximately 3.044 times AA genotype having (*p: 0.014 OR: 3.044, 95%CI: 1.205-7,688). A significant difference was found between rs6759180 RRM2 genotype distributions (*p: 0.033) and were determined increases the risk of disease approximately 3.49 times GG genotype having (p: 0,009 OR: 3, 49, %95CI:1.291-9,482). It was found significant difference in serum 8-OHdG levels between patients and controls (*p: 0001).